Pengaruh Pemasaran 7-P (Product, Price, Place, Promotion, People, Physical Evidence, Procces) Terhadap Keputusan Pembelian Supermarket Retail Jawa Tengah - Sri Heneng Prasastono; Heni Dwi Listyaningrum; Galuh Aditya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
Main problem: The influence of 7-P marketing (Product, Price, Place, Promotion, People, Physical Evidence, Process) on purchasing decisions. Objective: Analyze the influence of 7-P Marketing on Purchasing Decisions. Originality: The Influence of 7-P Marketing (Product, Price, Place, Promotion, People, Physical Evidence, Process) on Purchasing Decisions. Method: An important examination technique used in this exploration is the explanation strategy. Result: The combination of the 7P views (item, cost, place, progress, individual, physical evidence, process) influences purchasing choices, with the greatest impact covered by tangible evidence factors and the smallest impact is the cost variable. The details of the advertising system obtained are: following the spatial plan